PENGARUH MOTIVASI KERJA, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Bagian Operasional PT. Jasco Logistics) - Arzani, Luthfy Adzan; Poerbo, Suryadi; Setyadi, Dody (Politeknik Negeri Semarang, 2018)
This research is aimed to know the influence of work motivation, compensation and work environment toward performance of operational employee in PT. Jasco Logistics. The methods of data collection are interview and questionnaire completion. The sample of this research are 73 respondents and analytical method used are the validity test, reliability test, multiple linear regression conducted with the Ordinary Least Square (OLS) test methods and Goodness of Fit Test The result of regression analysis indicates that work motivation, compensation and work environment have positive influence on performance of employee. Based on t test it is indicated that eadership, motivation, work discipline have positive significant influence on performance of employee. Based on F test, independent variables simutaneuosly influence the performance of employee significantly, with coeficient of determination (R2) of 0,679. This means that 67,9% of performance of employee could be influenced by work motivation, compensation and work environment, while remaining 38,1% is influenced by other variables which are not observed